Long‐term hepatitis B surface antigen (HBsAg) kinetics during entecavir treatment in Korean patients—Functional cure unlikely. Issue 9 (17th May 2020) - Cho, Ju‐Yeon; Sohn, Won; Paik, Yong‐Han; Gwak, Geum‐Youn; Choi, Moon Seok; Lee, Joon Hyeok; Koh, Kwang Cheol; Paik, Seung Woon; Park, Chan Guk
Abstract: The aim of this study was to investigate the on‐treatment kinetics of quantitative HBsAg during entecavir therapy to predict the treatment period needed to achieve functional cure. From a cohort of 1009 CHB treatment‐naïve patients who were started on entecavir, the kinetics of quantitative HBsAg decline was assessed in 410 patients by a linear mixed model. The difference in the kinetics of quantitative HBsAg was determined based on the HBeAg positivity, HBeAg seroclearance and presence of baseline liver cirrhosis. Among the 410 patients, 213 patients (52.0%) were HBeAg‐positive and 217 patients (66.1%) were male with a median age of 48 years. During a median follow‐up of 53.5 months, the quantitative HBsAg level showed a slow but consistent decrease. The expected log qHBsAg levels as a function of time during entecavir treatment in HBeAg(+) and HBeAg(−) patients were 3.4773‐0.0039 × Months and 3.1853‐0.0036 × Months, respectively. The estimated time to clearance of quantitative HBsAg in our study was greater than 74.1 years in HBeAg‐positive patients and 73.5 years in HBeAg‐negative patients. The calculated time to achieve functional cure is lifelong without regard to HBeAg seroclearance or presence of liver cirrhosis. The mathematical modelling from a long‐term follow‐up of chronic hepatitis B patients on entecavir shows that HBsAg clearance requires decades of treatment. Thus, lifelong therapy is inevitable in entecavir‐treated patients to achieve functional cure.